Automatic acquisition and analytic procedure of acupuncture manipulation based on optical navigation - Zhang, Changshuai; Feng, Zihao; Chang, Weichao; Ma, Weigang; Wu, Yongjian; Li, Haiming; Pan, Xingfang; Ren, Haiyan; Liu, Yangyang; He, Zhaoshui; Tan, Wenjun (Zhōngguó zhēnjiǔ, 2025)
This paper presents an automatic acquisition and analytic procedure of acupuncture manipulation based on optical navigation, aiming at solving the shortcomings of existing acquisition methods of acupuncture manipulation. An acquisition holder installed at the handle tail of filiform needle was designed to display the movement trajectory of the needle during acupuncture delivery by collecting the movement trajectory of holder. The 3-month old male Bama miniature pig was selected as the experimental subject, and 6 points, "Bojian" "Qiangfeng" "Housanli" "Xiaokua" "Huiyang" (BL35) and "Baihui" (GV20), were selected during acupuncture manipulation. The optical navigation system was used to collect the real-time data, and these data were per-processed and analyzed using mean filtering and Fourier transform. The acupuncture procedure was divided into 3 stages, inserting, lifting-thrusting, and twisting. The results showed that the accuracy was 96.3% at lifting-thrusting stage, and that was 100.0% at twisting stage.